Narratives of Environmental Change: Mangroves, Shrimp Farming and Artisanal Fishing Communities in Ecuador - Carter, Eric (My University, 1999)
In recent years, many developing nations have reaped an economic windfall from the growth of shrimp aquacultute. Increasing demand for specialty seafood in the industrialized world, as well as a drive to diversify export commodities, has led to extensive construction of shrimp ponds in tropical areas, largely at the expense of coastal mangrove forests. Since the 1980s, Ecuador has become one of the world's leading shrimp exporters, exacting a high toll on the environment and transforming the economic basis of many coastal communities. Ecuadorian shrimp farmers dismiss their critics by asserting that the shrimp, industry has generated dynamic economic growth and employment opportunities for thousands of people. However, this paper will argue that transformation of mangrove estuaries brought on by the development of the shrimp industry has had uneven socioeconomic consequences. Specifically, traditional fishing communities have borne the greatest hardship from this rapid transformation, but simultaneously have found few sources of alternate employment in shrimp aquaculture. This study will focus on the estuaries of El Morro and Data de Posorja in southern Guayas province, which were dominated by small-scale economic activities such as artisanal fishing until the advent of shrimp farming. More than simply a conflict of social groups over a natural resource, this is also a story of dashing narratives. While many view the development of shrimp aquaculture as a story of progress and modernization, traditional fishermen see it as a story of betrayal and decline. The kind of story that prevails will have implications for future management of mangrove estuaries.
Includes figures, photographs, maps, bibliography and appendices
Keywords: Environmental change; Ecuador